"Flabulously" femme: Queer fat femme women's identities and experiences. Issue 4 (2nd October 2018) - Taylor, Allison
ABSTRACT: This article explores how queer fat femme women experience, negotiate, and resist heteronormativity, misogyny, and fatphobia, alongside other intersecting oppressions. By analyzing fat femmes' narratives presented in blogs and personal essays, this article examines themes including: the role of femme in fat queers (re)claiming femininities, the masculinizing and/or feminizing effects of "fatness" for queer femmes, the mutual constitution of fatphobia and femmephobia, femme fa(t)shion, fat femme (in)visibility, and the importance of intersectional conceptions of queer fat femininities. In doing so, this article argues that "queer fat femme" subjectivities offer fat and femme queers unique and significant opportunities for articulating resistant subjectivities, creating communities, and challenging oppressions.